2017
DOI: 10.48550/arxiv.1705.10602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-consistent investment and consumption strategies under a general discount function

Abstract: The paper [12] examines a concept of equilibrium policies instead of optimal controls in stochastic optimization to analyze a mean-variance portfolio selection problem. We follow the same approach in order to investigate the Merton portfolio management problem in the context of non-exponential discounting, a context that give rise to time-inconsistency of the decision maker. Equilibrium policies are characterized in this context by means of a variational method which leads to a stochastic system that consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This consequence generalizes the result obtained by Alia et al [3] to an incomplete market setting. The random field (p, q) satisfies a "flow" of BSDEs (3.13) with the additional condition (3.14) imposed on the diagonal terms (p s s , q s s ).…”
Section: A Necessary Condition For An Equilibrium Pairsupporting
confidence: 90%
See 4 more Smart Citations
“…This consequence generalizes the result obtained by Alia et al [3] to an incomplete market setting. The random field (p, q) satisfies a "flow" of BSDEs (3.13) with the additional condition (3.14) imposed on the diagonal terms (p s s , q s s ).…”
Section: A Necessary Condition For An Equilibrium Pairsupporting
confidence: 90%
“…(3) 2 are bounded, and λ 1 , λ 2 are of the forms λ 1 (t, s) = λ(s − t) and λ 2 (t) = λ(T − t) for some Lipschitz continuous function λ, then our model becomes (essentially) the same one as in Alia et al [3]. They suggested that in this setting an open-loop equilibrium control is characterized by a flow of FBSDEs.…”
Section: The Modelmentioning
confidence: 89%
See 3 more Smart Citations